2002
DOI: 10.1089/10755530260511748
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and Bronchial Asthma: A Long-Term Randomized Study of the Effects of Real Versus Sham Acupuncture Compared to Controls in Patients with Bronchial Asthma

Abstract: In view of the fact that the effects after real and sham acupuncture compared to controls who had no needling at all were small, in all likelihood clinically irrelevant, our data do not seem to support the use of acupuncture in the management of pharmacologically well-treated patients with mild-to-moderate persistent asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 23 publications
1
22
0
4
Order By: Relevance
“…11 The efficacy of acupuncture in asthma has been evaluated in several randomized controlled trials. [12][13][14][15][16][17][18][19][20][21][22][23][24] Few data are available for rhinitis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…11 The efficacy of acupuncture in asthma has been evaluated in several randomized controlled trials. [12][13][14][15][16][17][18][19][20][21][22][23][24] Few data are available for rhinitis.…”
mentioning
confidence: 99%
“…On the basis of the methodologic quality of the studies, the authors concluded more than 10 years ago that beneficial effects of acupuncture were more likely to be found in the low-quality studies (small sample, not randomized, and inadequate analysis). Looking at the available literature (Table III), [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] many studies have an inadequate methodology (ie, a Jadad score of less than 3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…randomised, controlled and blinded) [18][19][20][21][22][23][24][25][26], the effects of acupuncture are not different from the placebo treatments. Of note, only in two studies [21,26] transient and mild benefits were demonstrated. Thus, the conclusion derived from meta analysis studied and clinical trials is that acupuncture is not effective to treat asthma.…”
Section: Acupuncturementioning
confidence: 99%
“…Medici et al [47] studied 66 asthmatic patients in a randomized, single-blinded, controlled study who received either acupuncture, sham acupuncture, or no acupuncture in addition to conventional medications. Only the blood eosinophil count at 4 months showed a significant reduction in the real acupuncture group compared with the sham acupuncture group.…”
Section: Acupuncturementioning
confidence: 99%